INVESTIGAÇÕES SÔBRE A FEBRE Q EM SÃO PAULO - Valle, Luiz Augusto Ribeiro do; Brandão, Helvécio; Christovão, Dácio de Almeida; D´Apice, Mário (Arquivos da Faculdade de Higiene e Saúde Pública da Universidade de São Paulo, 1955)
The results of investigations concerning Q fever in cattle ranchers, dairy workers and cattle of the state of São Paulo are here reported. The serologic data here presented confirm and amplify those previously reported. 1) By using the specific complement fixation test, sera of 71 cattle ranchers or dairy workers, belonging to 8 different establishments, were studied. Of these 71 serums, 65 were negative, I anticomplementary and 5 positive: two at a titeroflin 8 and three at a ti ter o f I in 16. 2) Tests of a second serum from 20 dairy workers showed no significant difference from the first examination when performed forty five days later. A similar result was obtained in the study of the sera of two ranchmen, when examined a second time after an interval of about nine months. 3) Sera from 581 animais belonging to 9 different herds were studied. Of 171 bovine sera studied , 131 were negative, 16 anticomplementary and 24 positive, 16 at a titer of I in 16, 5 at I in 32, 2 at I in 64 and 1 at 1 in 256. 4) Two heifers from one o f the herds had ser a positive at 1 in 32 and 1 in 64; they showed a drop in titer, about two months later, to 1 in 4 and 1 in 32, respectively. The results of the tests performed with sera from 12 other animais of the same herd, negative in the first bleeding at a titer of 1 in 8, did not show significantly different results about five months later. 5) Attempts to i);olate Coxiella burnetii from two samples of blood, one of milk and one of placenta from bovines belonging to two of the 9 herds, failed. 6) Of 26 sera of recently imported bovines from other countries (Netherlands and Great Britain), 18 were negative, 2 anticomplementary and 6 positive, 5 at a titer of 1 in 16 and 1 at a titer of 1 in 32.